Characterization of BAT activity in rats using invasive and non-invasive techniques. - Andreas Paulus; Petronella A van Ewijk; Emmani B M Nascimento; Marijke De Saint-Hubert; Geert Hendrikx; Andrea Vogg; Ivo Pooters; Melanie Schnijderberg; Joris Vanderlocht; Gerard Bos; Boudewijn Brans; Vera B Schrauwen-Hinderling; et al. (PLoS ONE, 2019)
Introduction Brown adipose tissue (BAT) is considered as a potential target for combating obesity in humans where active BAT metabolizes glucose and fatty acids as fuel resulting in heat production. Prospective studies in humans have been set up to further study the presence and metabolic activity of BAT mostly using Positron Emission Tomography (PET) imaging in cold-stimulated conditions with the radiolabeled glucose derivative [18F]FDG. However, radiotracers beyond [18F]FDG have been proposed to investigate BAT activity, targeting various aspects of BAT metabolism. It remains questionable which tracer is best suited to detect metabolic BAT activity and to what extent those results correlate with ex vivo metabolic BAT activity. Methods PET and Single Photon Emission Computed Tomography (SPECT) imaging, targeting different aspects of BAT activation such as glucose metabolism, fatty acid metabolism, noradrenergic stimulation, blood perfusion and amino acid transport system, was performed immediately after injection of the tracer in rats under different temperatures: room temperature, acute cold (4 ⁰C for 4 h) or acclimated to cold (4 ⁰C for 6 h per day during 28 days). Furthermore, Magnetic Resonance Spectroscopy (MRS)-derived BAT temperature was measured in control and cold-acclimated rats. Results At room temperature, only [18F]FDG visualized BAT. Glucose metabolism, fatty acid metabolism, noradrenergic stimulation and blood perfusion showed a clear tracer-dependent twofold increase in BAT uptake upon cold exposure. Only the tracer for the amino acid transport system did not show BAT specific uptake under any of the experimental conditions. MRS demonstrated that cold-acclimated animals had BAT with a stronger heat-production compared to control animals. Conclusion BAT activity following cold exposure in rats was visualized by several tracers, while only [18F]FDG was also able to show BAT activity under non-stimulated conditions (room temperature). The variances in uptake of the different tracers should be taken into account when developing future clinical applications in humans.